Determinants of Patient Satisfaction in an Academic Rheumatology Practice. Issue 5 (August 2015) - Ku, Jennifer H.; Danve, Abhijeet; Pang, Helena; Choi, Dongseok; Rosenbaum, James T.
Abstract : Background: Although patient satisfaction is used as a measure of physician performance and is an essential component of chronic disease management, there is limited understanding about factors affecting satisfaction in rheumatologic settings. Objective: Our study aimed to identify factors affecting satisfaction in outpatients with rheumatic diseases by correlating satisfaction with various factors. Methods: We conducted a cross-sectional cohort study of rheumatology patients at Oregon Health & Science University in 2013. Patient satisfaction ratings were obtained, and data were collected from medical records. Descriptive and quantile regression analyses were performed to describe the population and to model predictors of satisfaction. Results: We obtained data from 573 patients, 76% were females, 92% were non-Hispanic white, with a mean age of 50 (SD, 15) years. Female gender (β = 7.51; 95% confidence interval [CI], 6.16–8.86), older age (β = 0.10; 95% CI, 0.01–0.20), and follow-up visit (β = 4.04; 95% CI, 0.14–7.93) had a positive impact on satisfaction, whereas polymyalgia rheumatica (β = −9.25; 95% CI, −15.25 to −3.25), arthralgia (β = −8.67; 95% CI, −16.60 to −0.74), myalgia (β = −8.67; 95% CI, −16.60 to −0.74), gout (β = −7.5; 95% CI, −14.13 to −0.89), ankylosing spondylitis (β = −5.20; 95% CI, −9.65 to −0.75), pain (β = −4.62; 95% CI, −8.43 to −0.81), fibromyalgia (β = −4.62; 95% CI, −7.80 to −1.44), longer visit duration (β = −0.08; 95% CI, −0.13 to −0.03), and afternoon appointments (β = −4.62; 95% CI, −7.04 to −2.20) had an inverse effect. Conclusions: Factors contributing to satisfaction scores differed for median satisfaction level and lower satisfaction level. Most of the factors identified as influencing patient satisfaction were unrelated to the physician or the skills of that physician.